Thermostable Chitinase Producing Bacterium from Ijen Hot Spring – Indonesia: Isolation, Identification, and Characterization - Chrisnasari Ruth; Priscilla Sutanto Liony; Paulina Dian; Wahjudi Alicia; Pantjajani Tjandra (E3S Web of Conferences, 2023)
The high industrial demand for thermostable chitinase with new and desirable characteristics has led to the exploration of chitinolytic bacteria from extreme environments. Therefore, this study aimed to isolate, screen, and identify chitinase–producing bacteria from Ijen hot spring, Indonesia. The highest chitinolytic activity bacterium was identified by 16S rRNA gene sequencing and its characteristics were confirmed by morphological and physiological analyses. Chitinase production activity of selected bacterium under variation of agitation and aeration as well as its chitinase properties were characterized afterward. Twelve chitinolytic bacterial colonies were isolated and screened for their growth activity on Thermus colloidal chitin medium, in which chitin was used as the sole carbon source. Among these twelve isolates, isolate B2 showed the highest chitinolytic activity. The molecular, morphological, and physiological analyses confirmed that isolate B2 belonged to Bacillus licheniformis. This isolate produced a huge amount of chitinase on Thermus colloidal chitin medium at 50 °C within 30 h. The highest growth and chitinase production activity were recorded at 3 vvm aeration rate and 300 rpm agitation speed. Chitinase produced by this isolate was optimally active at pH of 7 and temperature of 55 °C and evidently proofed as thermostable due to its high residual activity after several thermal stability tests.